PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM MENINGKATKAN EFISIENSI OPERASIONAL PENDIDIKAN - Iqbal, Muhammad; Ramadhan, Fajar (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
The use of Information and Communication Technology (ICT) has become a key step in enhancing efficiency in the education sector. This research aims to evaluate the impact of ICT implementation on the effectiveness of educational institutions and to identify the factors contributing to its adoption. The research methodology employed is qualitative, including in-depth interviews with teaching staff, employees, as well as management and administrators at secondary schools and universities.The findings of the study indicate that the use of ICT, such as Learning Management Systems (LMS), classroom management software, and online collaboration tools, improves performance. For instance, the use of LMS streamlines the management of learning materials, assessments, and communication between teachers and students. Meanwhile, school management software helps simplify administrative tasks, reduces manual work, and enhances information accessibility.However, the success of ICT implementation heavily relies on various factors, including infrastructure preparedness, ICT training and skill development for employees, and support from top management. This study concludes that with proper investment in infrastructure and human resources, ICT can be a highly effective tool in enhancing educational performance.